(untitled) (Eurasian Journal of Ecology, 2026)
This article examines the hydrogeological conditions of formation and spatiotemporal dynamics of fresh groundwater lenses in sandy massifs of the Atyrau and West Kazakhstan regions. The feasibility of targeted use of sub-dune lenses of fresh groundwater for pasture irrigation and drinking water supply is substantiated. It is established that, under certain soil, hydrogeological, and climatic conditions, such lenses are capable of providing a stable water supply for standard transhumance areas. A method for the rational exploitation of sub-dune lenses of fresh groundwater floating on zonal waters is proposed. This method utilizes a gentle water extraction method, allowing for long-term operation without degrading groundwater quality. A study of the natural conditions, hydrogeological characteristics of sand massifs, and a summary of available scientific data demonstrate the high potential for targeted development of the fresh groundwater lens in Western Kazakhstan. The proposed approach represents a fundamentally new, comprehensive solution to the problem of water supply for transhumance and offers significant socioeconomic potential by integrating local water resources into economic circulation. It has been shown that the use of the author’s method of gentle operation ensures the preservation of the hydrodynamic equilibrium of the lens, prevents the drawing in of underlying mineralized zonal waters and reduces the risk of siltation of the filter zone of wells. Key words: groundwater lenses, sand massifs, pasture irrigation, mineralization.